Convergent close-coupling approach to positron scattering on He+ - Rawlins, C.; Kadyrov, Alisher; Bray, Igor (Springer, 2018)
© 2018, EDP Sciences, SIF, Springer-Verlag GmbH Germany, part of Springer Nature. Abstract: A close-coupling method is used to generate electron-loss and total scattering cross sections for the first three partial waves with both a single-centre and two-centre expansion of the scattering wave function for positron scattering on He+. The two expansions are consistent with each other above the ionisation threshold verifying newly-developed positronium-formation matrix elements. Below the positronium-formation threshold both the single- and two-centre results agree with the elastic-scattering cross sections generated from the phase shifts reported in previous calculations. Graphical abstract: [Figure not available: see fulltext.].